2010
DOI: 10.1111/j.1365-2648.2009.05171.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing contact and gaining trust: an exploratory study of care avoidance

Abstract: Care providers who establish contact and win trust employ 'non-judgemental appreciation'. They start from the acceptance of what is and try to connect with the client and their world. These professionals use their initial actions to identify and praise qualities and achievements of clients. This style of work is supported by a set of deep-rooted personal qualities we can summarize as 'empathy'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
1
29
0
4
Order By: Relevance
“…(Martins 2008) These specific behavior changes have been associated with lower satisfaction with care,(Weiss and Ramsey 1989; Benkert, Peters et al 2006; Benkert, Hollie et al 2009; van Walraven, Oake et al 2010) lower adherence to treatment recommendations,(Altice, Mostashari et al 2001; Bickell, Weidmann et al 2009; van Walraven, Oake et al 2010) worse self-reported health,(Lee and Lin 2009) reduced willingness to seek care,(O’Malley, Mandelblatt et al 1997; Schout, de Jong et al 2010) and lower quality relationships with care providers. (Altice, Mostashari et al 2001; Benkert, Peters et al 2006; Stefanacci and Guerin 2013)…”
Section: Introductionmentioning
confidence: 99%
“…(Martins 2008) These specific behavior changes have been associated with lower satisfaction with care,(Weiss and Ramsey 1989; Benkert, Peters et al 2006; Benkert, Hollie et al 2009; van Walraven, Oake et al 2010) lower adherence to treatment recommendations,(Altice, Mostashari et al 2001; Bickell, Weidmann et al 2009; van Walraven, Oake et al 2010) worse self-reported health,(Lee and Lin 2009) reduced willingness to seek care,(O’Malley, Mandelblatt et al 1997; Schout, de Jong et al 2010) and lower quality relationships with care providers. (Altice, Mostashari et al 2001; Benkert, Peters et al 2006; Stefanacci and Guerin 2013)…”
Section: Introductionmentioning
confidence: 99%
“…This view of the metaparadigm of nurse builds on the concept definition found in Peplau's Theory of Interpersonal Relations; where nursing is described as a therapeutic interpersonal process between the nurse and patient. There is a synergy between the nurse and the patient that facilitates growth in both parties (Schout, De Jong, & Zeelen, 2010).…”
Section: Holism and The Bio-psycho-social Modelmentioning
confidence: 99%
“…Patients and their families say the manner in which they are listened to and cared for with compassion is highly valued, and matters just as much as the quality of health care itself (Bray et al, 2014;Lown et al, 2011;Schout et al, 2009). Compassionate care addresses the patient's core need for 'connection and relationships and is based on attentive listening and a desire to understand the patient's context and perspective ' (Lown et al, 2011).…”
Section: Compassion Is An Essential Ingredient In Quality Carementioning
confidence: 99%